Causas de tipo alimentario de angioedema y su relación con los niveles de inmunoglobulina E (IGE). - Marín Sisalima, Fausto Miguel (2017)
Allergy is an exaggerated reaction of the body that recognizes as strange a substance that is harmless to most people, this is called an allergen. When it enters the body of an allergic subject, the immune system responds by producing a large amount of antibodies called immunoglobulin E (IgE). In recent years, the prevalence of food allergies has aroused great interest. Currently, it is estimated that 2 to 4% of adults and 6% of children suffer from some form of food allergy. Angioedema is characterized by rapid swelling of the skin, mucous membranes and submucosal tissues. Its clinical picture can be induced by multiple causes such as: food, inhalants, medications and others. The objective of the present investigation is to determine the most frequent food allergen inducing angioedema, as well as to establish age, gender and correlation with serum IgE levels. The present investigation was performed in a total of 92 patients with clinical diagnosis of angioedema. All of them were Prick Test using 7 food antigens (citrus, peanut, egg, milk, tomato, seafood and strawberry), then the serum levels of IgE were measured in each of the patients. The results were as follows: the most common foods inducing angioedema were, first citrus, followed by seafood and third milk alongside the strawberries. In relation to age, the largest number of allergic patients are aged between 1 and 15 years; followed by patients aged between 16 and 30 years and finally those who were between 31 and 45 years old. Taking into account the IgE variable, it was observed that 98.9% of patients had increased levels of serum IgE. Likewise, correlating these levels with the most frequent food antigen, it was determined that there is a direct relationship with the presence of hypersensitivity to citrus fruits, then to seafood and thirdly to dairy and strawberries. Keywords: angioedema, IgE, food antigens.